Peroxisome proliferator‐activated receptor γ agonists reduce cell proliferation and viability and increase apoptosis in systemic sclerosis fibroblasts. (5th October 2012) - Antonelli, A.; Ferri, C.; Ferrari, S.M.; Colaci, M.; Ruffilli, I.; Sebastiani, M.; Fallahi, P.
Summary Background No study has evaluated the effect of the peroxisome proliferator‐activated receptor γ (PPARγ) agonists on cell viability, proliferation and apoptosis in cultured systemic sclerosis (SSc) fibroblasts. Objectives The effects of two pure PPARγ agonists (rosiglitazone and pioglitazone) in cultured SSc fibroblasts were evaluated and compared with effects in normal fibroblasts. Methods The study included evaluation of cell viability and proliferation (based on the cleavage of tetrazolium salts and measurement of absorbance of the cell proliferation reagent WST‐1), and determination of cell apoptosis (by means of the Hoechst dye uptake). Results Rosiglitazone or pioglitazone (20 μmol L−1) significantly reduced cell proliferation (cell count of 75% and 83% compared with baseline, respectively, after 2 h) and cell viability (absorbance reductions of 25% and 22% compared with baseline, respectively, after 2 h), and increased apoptosis (apoptotic cell percentages 9·9% and 8·6%, respectively, after 48 h of incubation) in SSc fibroblasts, whereas they did not present a significant influence on control fibroblasts. Conclusions The effects of rosiglitazone or pioglitazone shown on SSc fibroblasts raise the hypothesis of a therapeutic role for PPARγ agonists in patients affected by SSc.